ANTIOXIDANT AND ANTI-STRESS EFFECTS OF NAX SEOLITE (International journal of artificial intelligence, 2026)
This article analyzes the antioxidant and anti-stress effects of NaX zeolite. Due to its high adsorption and ion-exchange properties, NaX zeolite reduces free radical formation, limits the absorption of toxic substances, and mitigates the negative effects of stress factors on the organism. Special attention is paid to the prospects of using NaX zeolite in veterinary practice to stabilize metabolic processes, support immune function, and reduce oxidative stress in animals.